Financial analysis of the broadcasting service of digital television, radio programs and data transmission in the Republic of Serbia - Cerovina, Jelena; Milošević, Ivana; Simić, Milan (The European Journal of Applied Economics, 2022)
Digitalization of radio and television programs as well as other multimedia content is a very complex process with many aspects and requires large financial investments in the infrastructure of the system and all supporting elements. This paper provides a concise description of the institutional and regulatory frameworks in the digitalization process in the Republic of Serbia, the important reasons related to the choice of compression standard and standard for the transmission of television signals, as well as a description of the role of JP Emisiona tehnika i veze in the digitalization process. The aim of this paper is the financial analysis of earnings on an annual basis for the services of broadcasting TV programs in the first and second multiplexes, broadcasting radio programs within the DVB-T2 network and data transmission services after the digitalization process. The method and data required for the preparation of the financial analysis were derived on the basis of the price list of services published by the JP Emisiona tehnika I veze published in August 2020. The results are presented tabular and graphically.
Keywords: digitalization, digital television, digital data transmission, DVB-T2, financial analysis